2021
DOI: 10.3389/fpsyg.2021.727887
|View full text |Cite
|
Sign up to set email alerts
|

How and When Health-Promoting Leadership Facilitates Employee Health Status: The Critical Role of Healthy Climate and Work Unit Structure

Abstract: Health-promoting leadership has attracted a lot of attention from scholars in recent years. However, majority studies focused on theoretical arguments rather than empirical examination. Not only that, extant research often theorizes health-promoting leadership as a combination of a series of direct and explicit health-related behaviors, neglecting the potential social information it may convey to employees. Based on social information processing theory, this study empirically examines how and when health-promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Our health is, without a doubt, the single most asset that any one person can have. This is true for most of us ( 1 ). Despite this, however, there are occasions when things go wrong in practice and the patients wind up getting hurt while they are receiving treatment at the healthcare facility ( 2 ).…”
Section: The Importance Of Healthmentioning
confidence: 75%
“…Our health is, without a doubt, the single most asset that any one person can have. This is true for most of us ( 1 ). Despite this, however, there are occasions when things go wrong in practice and the patients wind up getting hurt while they are receiving treatment at the healthcare facility ( 2 ).…”
Section: The Importance Of Healthmentioning
confidence: 75%
“…Related studies have confirmed that health-oriented leadership, health awareness, health value, and health behavior scores were significantly associated with individual employee depression and anxiety symptoms [34]. Along the same lines, organizational climate is found to be an important part of the work environment [35]. HC, the sum of health resources, health elements, and health-centered communication in an organization [36], impacts employees' health [37].…”
Section: Health-promoting Leadership and Health Climatementioning
confidence: 88%
“…A five-point Likert-scale was used, from 1 ("strongly disagree") to 5 ("strongly agree"). The Chinese version of HPL demonstrated high reliability and validity [35,61]. The reliability range of the HPL questionnaire is 0.84 to 0.88.…”
Section: Health-promoting Leadershipmentioning
confidence: 99%
“…When considering a manager’s learning and career development together, the question becomes to what extent research studies that use these theoretical starting points, that is, learning theory and career development theory, take into account the unique conditions that characterize managerial work and how it contributes to our understanding of what it is that could make a managerial position feel sustainable? When talking about sustainability in managers, it is common to refer to managers’ leadership and how they create a sustainable balance for their employees, for example, between engagement, productivity, learning and well-being (Eldor, 2017; Liu et al , 2021; Nikolova et al , 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%